Multiphasic strain differentiation of atypical mycobacteria from elephant trunk wash - Kok-Gan Chan; Mun Fai Loke; Bee Lee Ong; Yan Ling Wong; Kar Wai Hong; Kian Hin Tan; Sargit Kaur; Hien Fuh Ng; MFA Abdul Razak; Yun Fong Ngeow (2015)
Background. Two non-tuberculous mycobacterial strains, UM_3 and UM_11, were isolated from the trunk wash of captive elephants in Malaysia. As they appeared to be identical phenotypes, they were investigated further by conventional and whole genome sequence-based methods of strain differentiation.